Implementation study of an interprofessional medication adherence program for HIV patients in Switzerland: quantitative and qualitative implementation results - Mélanie Lelubre; Olivier Clerc; Marielle Grosjean; Karim Amighi; Carine De Vriese; Olivier Bugnon; Marie-Paule Schneider (BMC, 2018)
Abstract Background An interprofessional medication adherence program (IMAP) for chronic patients was developed and successfully implemented in the community pharmacy of the Department of ambulatory care and community medicine (Lausanne, Switzerland). This study assesses the capacity of a physician and a nurse at the infectious diseases service of a public hospital and of community pharmacists in the Neuchâtel area (Switzerland) to implement the IMAP in their practice. Methods Mixed method, prospective, observational study. Quantitative and qualitative analyses of the implementation process were conducted following the RE-AIM model (reach, effectiveness, adoption, implementation and maintenance). Results Implementation started in November 2014. One physician, one nurse, and five pharmacists agreed to participate. Healthcare professionals perceived the benefits of the program and were motivated to implement it in their practice (adoption). Seventeen patients were included in the program; 13 refused to participate. The inclusion of naïve HIV patients was easier than the inclusion of experienced patients with difficult psychosocial issues (reach). Pharmacists were engaged in reinforcing patient medication adherence in 25% of interviews (effectiveness). Key facilitators expressed by healthcare professionals were patient inclusion by the physician and the nurse instead of the pharmacist and the organisation of regular meetings between all stakeholders. In contrast, the encountered barriers were the lack of time and resources, the lack of team uptake, and the lack of adoption by senior managers (implementation). Interviewed patients were all satisfied with this new program, encouraging healthcare professionals to scale it up. Structural changes allowed the hospital and one pharmacy to enter the maintenance stage (maintenance). Conclusion The research team and collaboration between all professionals involved played an important role in this implementation. However, the dissemination of such a program to a larger scale and for the long term requires financial and structural resources as well as transitional external support.